DEVELOPMENT OF CULTURE AND ENTERTAINMENT PARKS (American Journal of Pedagogical and Educational Research, 2023)
The Hanging Gardens of Babylon were one of the Seven Wonders of the Ancient World listed by Hellenic culture. They were described as a remarkable feat of engineering with an ascending series of tiered gardens containing a wide variety of trees, shrubs, and vines, resembling a large green mountain constructed of mud bricks. It was said to have been built in the ancient city of Babylon, near present-day Hillah, Babil province, in Iraq. The Hanging Gardens' name is derived from the Greek word κρεμαστός (kremastós, lit. 'overhanging'), which has a broader meaning than the modern English word "hanging" and refers to trees being planted on a raised structure such as a terrace